Tren dan Tantangan Manajemen Sumber Daya Manusia di Era Digital - Vitaharsa , Leonardo Indra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze trends and challenges in human resource management (HRM) in the digital era through a literature review approach. The research employs a Systematic Literature Review (SLR) based on the PRISMA model, analyzing 30 relevant articles published between 2020 and 2024. The findings indicate that organizations increasingly adopt HR digitalization, HR analytics, and Artificial Intelligence to enhance efficiency, data-driven decision-making, and employee skill development. Additionally, a focus on employee experience and digital learning-based competency development has become a key strategy to improve engagement and productivity. On the other hand, digital transformation brings challenges such as digital skill gaps, resistance to change, data privacy risks, and the phenomenon of the “Great Resignation.” These results highlight the importance of a balanced approach between technology and human-centered practices in modern HRM